Model Checking Embedded C Software Using k-Induction and Invariants - Rocha, Herbert; Ismail, Hussama; Cordeiro, Lucas; Barreto, Raimundo (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2015)
We present a proof by induction algorithm, which combines k-induction with invariants to model check embedded C software with bounded and unbounded loops. The k-induction algorithm consists of three cases: in the base case, we aim to find a counterexample with up to k loop unwindings, in the forward condition, we check whether loops have been fully unrolled and that the safety property ø holds in all states reachable within k unwindings, and in the inductive step, we check that whenever ø holds for k unwindings, it also holds after the next unwinding of the system. For each step of the k-induction algorithm, we infer invariants using affine constraints (i.e., polyhedral) to specify pre-and post-conditions. Experimental results show that our approach can handle a wide variety of safety properties in typical embedded software applications from telecommunications, control systems, and medical devices, we demonstrate an improvement of the induction algorithm effectiveness if compared to other approaches.